OPTIMASI PROSES EKSTRUSI MI JAGUNG DENGAN METODE PERMUKAAN RESPON [Optimization of Corn Noodle Extrusion Using Response Surface Methodology] - Tjahja Muhandri; Adil Basuki Ahza; Rizal Syarief; . Sutrisno (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Cooking loss and elongation are primary noodle quality parameters that depend on microstructure of the noodle. The noodle microstructure is strongly influenced by degree of gelatinization, moisture content, and shear force experienced by the dough. These parameters are controlled by temperature and screw speed of the extruder. The objective of this research was to optimize three processing variables i.e., corn flour moisture (70, 75, 80% dry basis), extruder temperature (80, 85, 90°C), and screw speed (110, 120, 130 rpm). Corn noodles were processed using Scientific Laboratory Single Screw Extruder type LE25-30/C. Optimizations Using Response Surface Methodology were based on four parameters, i.e., hardness, stickiness, elongation, and cooking loss characteristics .Results showed that the optimum processing condition was obtained at moisture of 70% (dry basis), extruder temperature 90°C, and screw speed 130 rpm. Under this condition, corn noodles has hardness of 3039.79 gf, stickiness of -116.2 gf, elongation of 318.68%, and cooking loss of 4.56%.